2015
DOI: 10.3103/s0361521915040059
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the preparation of coal-tar pitch

Abstract: The production of tar pitches and binding agents for the manufacture of high quality carbon materials is considered. The progressive scarcity of coal tar pitch is noted. The necessity of a search for new sources of raw materials and alternative methods for the production of coal tar pitch substitutes is substanti ated. The capabilities of different methods for the thermal and thermochemical processing of coals with the production of pitch like products are considered. The prospects of a low temperature process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…During thermal dissolution in the anthracene fraction of coal tar, the yield of pitch-bearing products is high for GZh and Zh coal, as we showed in [26][27][28]. The technical and structural properties of the pitch produced resemble those of hybrid pitches based on mixtures of coal tar and petroleum [29,30]. Their content of environmentally hazardous polycyclic aromatic hydrocarbons such as benzo(a)pyrene is 2-3 times less than that of the coke-plant pitch currently employed.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…During thermal dissolution in the anthracene fraction of coal tar, the yield of pitch-bearing products is high for GZh and Zh coal, as we showed in [26][27][28]. The technical and structural properties of the pitch produced resemble those of hybrid pitches based on mixtures of coal tar and petroleum [29,30]. Their content of environmentally hazardous polycyclic aromatic hydrocarbons such as benzo(a)pyrene is 2-3 times less than that of the coke-plant pitch currently employed.…”
Section: Introductionmentioning
confidence: 76%
“…The literature regarding the thermal dissolution of coal to produce high-boiling pitch was reviewed in [9,10]. Research at the Institute of Fossil Fuels and Kharkov Coal-Chemistry Institute has shown that the product yield in thermal dissolution is largely determined by the properties of the solvent and the activity of the coal [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is intensified at temperatures above 450°C, when polycondensed aromatic systems with a much bigger molecular mass (mesophase) are produced. 183,184 The viscosity significantly increases up to material solidification. Progressively ongoing dehydrogenation and structure ordering lead to socalled pitch coke (1000°C), and finally to graphite (ca.…”
Section: Pitchmentioning
confidence: 99%
“…The progressively developing technology for smelting high-quality steels in electric arc furnaces may also face the same problem because the preparation of the graphite electrodes will require significant amount of the same coal-tar pitch. In this context, there is growing interest in the production of the coal tar substitutes that are not dependent on the coking process [3][4][5]. The need to solve this challenge is reasoned also by a significant drawback of the commercial coal tar because of high content of the carcinogenic substances.…”
Section: Introductionmentioning
confidence: 99%